A Pragmatic Review of Learning Models Used for Unsupervised Analysis of Existing Cyber Physical Deployments from an Empirical Perspective - Sadrani , Varsha Haridas; Jagannadha Rao , G. V. V. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Cyber-physical deployments include game engines, multimedia systems, internet of Things (IoT) systems, etc. Each of these models has certain inputs, several processing layers, and certain outputs. Monitoring & control of such deployments can be automated via their unsupervised analysis, which requires deep learning & pattern analysis methods. A wide variety of such models are proposed by researchers and system designers, but each of them has its own nuances, advantages, limitations, & future research scopes. Moreover, these models have different performance characteristics, that vary in terms of analysis accuracy, precision, recall, fMeasure, delay of analysis, response time, computational complexity, etc. Thus, while deploying such learning models, researchers & system designers are required to perform manual analysis, validation, and testing for automation & control. Due to this cumbersome process, the cost & time to market for these unsupervised control models is very high, which limits their scalability, and deployment capabilities. To overcome this issue, a detailed characteristic discussion of these models is done in this text. Based on this discussion, researchers will be able to identify existing unsupervised & semi-supervised learning models, which closely match their deployments. These models are further analyzed in terms of their performance metrics, that includes, accuracy of analysis, response time needed for control, delay needed for analysis, precision of analysis, computational complexity, and cost of deployment. Using these metrics, researchers can evaluate best performing models for their deployments, which will assist them in reducing cost, and time needed for automating their cyber physical systems. This text also discusses certain future prospects that can be explored by researchers in order to further enhance quality of their deployments.